Clinical and epidemiological profile of newborns hospitalized in an Intensive Care Unit SARS-CoV-2 (Research, Society and Development, 2023)
Objective: to outline the clinical and epidemiological profile of newborns admitted to a SARS-CoV-2. Methods: this is a quantitative, descriptive, retrospective study of medical record review carried out in a maternity hospital located in the city of Teresina-PI. Medical records of newborns of both sexes with a maternal history of coronavirus infection were included. Medical records with many incomplete data (above 20) and medical records of newborns admitted to the unit with no maternal history of COVID-19 were excluded. Results: The total sample of this study consisted of 63 medical records of patients who met the established criteria, the majority being female (52.4%; n=33), without the presence of malformations (84.1%; n=53), preterm (82.5%; n=52), with adequate weight for the gestational age (73.0%) and with a moderate degree of discomfort in the Silvermam-andersen -BSA Bulletin (65.1%; n= 41). The main clinical manifestations of patients admitted to this neocovid unit were fever (19.0%;n=12) and dyspnea (15.9%;n=10).In addition, research reveals that preterm birth and breathing difficulties are possible complications arising from pregnancy in women with COVID-19. High rates of cesarean delivery were also observed. The need for ventilatory support in neonates may be associated with prematurity and not with SARS-CoV-2 infection. As it is a disease that has not yet had all its mechanisms revealed, it is important to emphasize the performance of new studies comparatives.